Detailed specification of the Arctic ionosphere and an application to three-dimensional raytracing - Buchau, J.; Wong, M.; Pike, Charles P.; Air Force Cambridge Research Laboratories (U.S.) (L.G. Hanscom Field, Bedford, Massachusetts : Air Force Cambridge Research Laboratories, Air Force Systems Command, United States Air Force, 1973)
A statistical analysis of Alouette topside ionograms shows that the probability of occurrence of the midlatitude F-layer trough is 100 percent in winter and at equinox, and is 50 percent in summer. The trough, which is generally centered on 55 degrees corrected geomagnetic latitude and which is about 5 degrees to 10 degrees wide, extends throughout the night hemisphere with f(o)F2 values less than 2 MHz. Comparison of the location of the trough to the area in which coverage by an over the horizon backscatter (OTHB) system is anticipated shows that the trough will adversely affect system performance in the northeast direction most of the night. An in-depth case study of the effects of the trough on HF propagation was made, based on an instantaneous three-dimensional description of the ionosphere. This description of the ionosphere was composed of cross sections showing ionospheric electron-density structure in the area northeast of the Polar Fox II site. Three-dimensional raytracing was applied to this description of the ionosphere, and the trough and the steep electron-density gradient at the poleward edge of the trough were found to adversely affect propagation of HF signals. (Modified author abstract). "Ionospheric Physics Laboratory Project 5631." AD0775084 (from http://www.dtic.mil). "27 November 1973." Includes bibliographical references (pages 27-28). A statistical analysis of Alouette topside ionograms shows that the probability of occurrence of the midlatitude F-layer trough is 100 percent in winter and at equinox, and is 50 percent in summer. The trough, which is generally centered on 55 degrees corrected geomagnetic latitude and which is about 5 degrees to 10 degrees wide, extends throughout the night hemisphere with f(o)F2 values less than 2 MHz. Comparison of the location of the trough to the area in which coverage by an over the horizon backscatter (OTHB) system is anticipated shows that the trough will adversely affect system performance in the northeast direction most of the night. An in-depth case study of the effects of the trough on HF propagation was made, based on an instantaneous three-dimensional description of the ionosphere. This description of the ionosphere was composed of cross sections showing ionospheric electron-density structure in the area northeast of the Polar Fox II site. Three-dimensional raytracing was applied to this description of the ionosphere, and the trough and the steep electron-density gradient at the poleward edge of the trough were found to adversely affect propagation of HF signals. (Modified author abstract). Mode of access: Internet.